Impact of pre-delivery medication treatment on delivery outcome in patients with primary immune thrombocytopenia: a cohort study - Xue Xu; Mei-Ying Liang; Lin-Rui Zhao; Jian-Liu Wang; Xiao-Hui Zhang (Platelets)
Background: Clinical research data showed a series of adverse events in the delivery period of primary immune thrombocytopenia (ITP) patients, including high cesarean section rate. Consensus report proposed that for patients with platelet count below 50 × 109/L, prednisone or intravenous immunoglobulins (IVIg) can be given to raise the platelet count in third trimester in preparation for labor.Objectives: To evaluate the effect of low-dose prednisone or IVIg therapy on delivery outcomes in patients with ITP.Study design: This was a cohort study that included pregnant women with ITP from January 2017 to December 2022. Patients with platelet counts of (20–50) ×109/L at the time of delivery (≥34 weeks) and who had not received any medication before were enrolled in the study. Patients were divided into the pre-delivery medication group (oral prednisone or IVIg) and untreated group according to their preferences. The differences in vaginal delivery rate, postpartum bleeding rate, and platelet transfusion volume between the two groups were compared using t-test, Wilcoxon rank-sum test, and χ2 test. Logistic regression analysis was used to identify the factors affecting vaginal delivery rate and postpartum bleeding rate, and multiple linear regression analysis was used to identify the factors affecting platelet transfusion volume.Results: During the study period, a total of 96 patients with ITP were enrolled, including 70 in the pre-delivery medication group and 26 in the untreated group. The platelet count of pre-delivery medication group was 54.8 ± 34.5 × 109/L, which was significantly higher than that of untreated group 34.4 ± 9.0 × 109/L (p = .004). The vaginal delivery rate of the medication group was higher than the untreated group [60.0% (42/70) vs. 30.8% (8/26), χ2 = 6.49, p = .013]. After adjusting for the proportion of multiparous women and gestational weeks, the results showed that medication therapy during the peripartum period was associated with vaginal delivery (OR = 4.937, 95% CI: 1.511–16.136, p = .008). The postpartum bleeding rates were 22.9% (16/70) and 26.9% (7/26) in the medication group and untreated group, respectively, with no significant difference between the two groups (χ2 = 0.17, p = .789), while the platelet transfusion volume was lower in the medication group than untreated group [(1.1 ± 1.0) vs. (1.6 ± 0.8) U].Conclusion: Pre-delivery medication therapy can increase vaginal delivery rate, reduce platelet transfusion volume, but does not decrease the incidence of postpartum hemorrhage.